Benefits of post-mastectomy radiation for T4N0M0 breast cancer patients: A SEER Database study. (2022) - Zhao, Ruipeng; He, Weiwei; Guan, Xiaoxiang
Highlights: Married statue, HR+/Her- and HR+/Her+ subtypes, and use of PMRT(post-mastectomy radiation therapy) were independent predictors of improved BCCS and OS. PMRT was beneficial for all subtypes of overall survival, but only for TNBC patients' breast cancer-specific survival. In T4N0M0 breast cancer patients, TNBC has the worst prognosis among all subtypes. Abstract: Purpose: To evaluate the impact of post-mastectomy radiation therapy (PMRT) in breast cancer patients with stage T4N0M0. Method: Patients diagnosed with breast cancer of T4N0M0 from Jan 2010 to Dec 2015 were extracted from SEER database. Multivariable logistic regression was used to analyze the factors associated with PMRT. Univariate and multivariate COX regression were used to analyze factors that might be associated with breast cancer specific survival (BCSS) and overall survival (OS) of patients. Kaplan–Meier analysis was performed to evaluate BCSS and OS in different subtypes of patients. Result: Multivariable logistic regression showed that patients ≥ 71 years were less intend to have PMRT. Multivariate Cox analysis showed that married statue, HR+/Her- and HR+/Her+ subtypes, were independent predictors of improved BCSS and OS, and use of PMRT could improve BCSS and OS . PMRT was beneficial for OS in all subtypes breast cancer patients, but BCSS benefit was observed only in TNBC patients. Conclusion: The use of PMRT improves OS in all T4N0M0 patients, but in terms of BCSS, it only beneficial for TNBC patients.